ELECTION OF GEAR OILS BY PHYSICO-CHEMICAL CHARACTERISTICS - Kindrachuk, Myroslav; Melnyk, Volodymyr; Leusenko, Daria; Herasymov, Volodymyr (Problems of Friction and Wear, 2023)
A comparative analysis of the performance of mineral and synthetic gear oils according to the main (standard) physical and chemical characteristics was carried out. The main requirements for gear oils, which are formulated today by leading gear manufacturers and are reflected in international specifications and standards, are given. Conclusions were made regarding the compatibility of mineral and synthetic gear oils.